Guilty repair sustains cooperation, angry retaliation destroys it - Skatova, Anya; Spence, Alexa; Leygue, Caroline; Ferguson, Eamonn (Nature Publishing Group, 2017)
Sustained cooperative social interactions are key to successful outcomes in many real-world contexts (e.g., climate change and energy conservation). We explore the self-regulatory roles of anger and guilt, as well as prosocial or selfish social preferences in a repeated social dilemma game framed around shared electricity use at home. We explore the proposal that for sustained cooperation, guilty repair needs to override angry retaliation. We show that anger is damaging to cooperation leading to retaliation and an increase of defection, while, through guilt, cooperation is repaired resulting in higher levels of cooperation. We demonstrate a disconnect, as a function of participant’s social preferences, between the experience of anger and subsequent retaliation. While there is no difference in reports of anger between prosocial and selfish individuals after finding out that others use more energy from the communal resource, prosocials are less likely to act on their anger and retaliate. Selfish individuals are motivated by anger to retaliate but not motivated by guilt to repair and contribute disproportionately to the breakdown of cooperation over repeated interactions. We suggest that guilt is a key emotion to appeal to, when encouraging cooperation.